1997
DOI: 10.1021/ja962807q
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Molecular Conformation, Dynamics, and Chemical Shift Anisotropy of α,α-Trehalose in D2O by NMR Relaxation

Abstract: A molecular dynamics study and solution-phase 1 H and 13 C chemical shift anisotropy determination of a symmetric cryogenic disaccharide, R,R-trehalose, has been performed in a temperature range between 264 and 350 K. Negligible temperature dependence of proton-carbon couplings of the asymmetrically [1-13 C]-labeled trehalose suggest that the averaged conformation of the interglycosidic linkage is centered around dihedral angles φ ) ψ ) -41°with (5°uncertainty. Homonuclear NOE-s in the labeled trehalose suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 67 publications
(59 reference statements)
9
42
1
Order By: Relevance
“…Since the three angles H CHC , u CH À u Z and h Z are interrelated, they were in the course of the fitting fixed at the tetrahedral values, and only Dr was adjusted. The values of Dr = 57.9 ± 1.5 at 323 K and Dr = 56.7 ± 1.5 at 343 K are in reasonable agreement with each other and in the range of the Dr value obtained for carbon-13 in other sugars [52][53][54]. The value of Dr is very sensitive to the value of h Z .…”
Section: Tablesupporting
confidence: 84%
“…Since the three angles H CHC , u CH À u Z and h Z are interrelated, they were in the course of the fitting fixed at the tetrahedral values, and only Dr was adjusted. The values of Dr = 57.9 ± 1.5 at 323 K and Dr = 56.7 ± 1.5 at 343 K are in reasonable agreement with each other and in the range of the Dr value obtained for carbon-13 in other sugars [52][53][54]. The value of Dr is very sensitive to the value of h Z .…”
Section: Tablesupporting
confidence: 84%
“…The testing of the force field for a more extensive set of mono-and disaccharides is in progress, and the results (including possible further refinement of the parameter set) will be reported in a forthcoming article. For trehalose: from X-ray crystallography (I: trehalose dihydrate; 91,92 II: anhydrous trehalose 93 ) and three independent NMR experiments (I, 94 II, 95 Note, finally, that two studies relying on of the present 45A4 carbohydrate force field have been reported. 87,88 In the first article, an early version of the force field was used to investigate the influence of methylation at specific hydroxyl groups on the stability of amylose and cellulose fragments.…”
Section: Resultsmentioning
confidence: 91%
“…The plot is reasonably linear and the derived activation energy, E a ¼ 24 AE 4 kJ mol À1 , is in good agreement with ab initio calculation by Tvaroska et al [48], who obtained the rotational barrier for methyl 2,3-dideoxy-b-D D -glucopyranoside of about 25-30 kJ mol À1 . For the sake of comparison, we show in the same diagram also the corresponding plot for the global correlation time, which for sugar solutions is known to follow the Arrhenius relation [27,51].…”
Section: Resultsmentioning
confidence: 99%